Pengaruh Jarak Angkut dan Grade Jalan Terhadap Biaya Operasional Alat Angkut dari Front Penambangan Menuju Dumping Area untuk Efisiensi Biaya Produksi pada Penambangan Batu Kapur Bulan Oktober 2019 di PT. Semen Padang - Vela Yulia; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Semen Padang uses an open mining system using the Quarry method, a heavy a heavy equipment used by PT. Semen Padang is a HD komatsu 785-7 conveyance for transporting limestone from the front to the crusher. fuel is a contributor to mining operating costs the biggest. The hauling distance from the PNBP 9 front to dumping around 2,1 Km i, and the road grade exceeds the company standard, the company standard for grade is 10%, while there are 17,8% of real estate in the road grade, with such hauling distance and grade will certainly affect the operational costs of hauling, the age of the equipment transport often suffers damage, so the costs incurred large seen from the maintenance and replacement of spareparts.This method utilizes a simple linear regression, the HD komatsu 785-7 hauling distance has a 93% influence and for the influence of HD komatsu 785-7 hauling road grade DK-16 units are 89%, DK-17 is 97%, DK-18 is 92% and DK-19 has an influence of 96%. For the DK-16 fuel consumption costs Rp. 124.896.510 DK-17 is Rp. 220.604.835, DK-18 is Rp. 67.737.900, and DK-19 is Rp. 145.370.100. For maintenance costs and spareparts DK-16 is Rp.98.861.500 DK-17 is Rp.99.931.629 DK-17 is Rp.189.447.578 DK-17 is Rp. 10.886.820.Keywords: Hauling Distance, Grade Of Road, Fuel Consumption Cost, Maintenance Cost, Sparepart Cost.